Molecular Imaging in Neurovascular Diseases: The Use of Ferumoxytol to Assess Cerebral Aneurysms and Arteriovenous Malformations. Issue 2 (April 2016) - Zanaty, Mario; Chalouhi, Nohra; Starke, Robert M.; Jabbour, Pascal; Hasan, David
Abstract : Abstract: Inflammation is increasingly being recognized as contributing to the underlying pathophysiology of cerebral aneurysms and brain arteriovenous malformation. Ferumoxytol is being increasingly used for both its prolonged intravascular imaging characteristics and its utility as an inflammatory marker when imaged in a delayed fashion. We aim to present a review article on the use of ferumoxytol to assess cerebral aneurysms and arteriovenous malformation. This could potentially help assist the physician in his judgment for intervening, as aneurysms that look macroscopically the same may behave differently.